Students’ Perception of the Free4talk Website as A Self-learning Media to Improve Speaking Skills of the First Year English Education Students at the University of Mataram - Paramadina, Yelsi; Sujana, I Made; Saputra, Agus (Program Studi Pendidikan Bahasa Inggris, 2025)
This research explores the perceptions of first-year students in the English Education Program at the University of Mataram regarding the use of Free4Talk as a self-directed learning platform to improve their English-speaking skills. In response to the growing need for flexible and accessible language learning tools, Free4Talk offers a real-time communication environment that allows users to engage in spontaneous conversations with global speakers. The study adopts a mixed-methods approach, combining quantitative data from student questionnaires and qualitative insights from semi-structured interviews to obtain a comprehensive understanding of student experiences and attitudes. The results reveal that most students perceive Free4Talk positively, especially in terms of enhancing their speaking fluency, vocabulary, pronunciation, and confidence. The platform’s ease of access, time flexibility, and informal setting were seen as major advantages that support learner autonomy. Students reported feeling more motivated and less pressured compared to traditional classroom settings, which enabled them to experiment with language more freely. However, the platform was found to lack structured content, goal-setting features, and pedagogical support, which are crucial for sustained progress and skill development. Despite its benefits, several challenges were identified, including technical difficulties such as unstable internet connections and poor audio quality, psychological barriers like fear of making mistakes and anxiety when interacting with strangers, as well as limited availability of serious and constructive conversation partners. The absence of feedback and measurable progress tracking also hindered students’ ability to monitor improvement. These findings suggest that while Free4Talk serves as a useful supplementary tool for speaking practice, it is not sufficient as a stand-alone learning medium. Therefore, its integration into formal instruction, guided by educators, could significantly enhance its effectiveness in fostering English-speaking proficiency among EFL learners.